Artificial intelligence - A tool for thermal design of cooling towers - Mohiuddin, A. K. M. (2003)
Artificial intelligence is concerned with symbolic solving of problems, or with constructing machines, capable of acquiring, storing and utilizing knowledge about the real and/or abstract world, and at the same time acting automatically, on the basis of adequate built-in models of the environment, as an intelligent being. Artificial intelligence seeks to provide a computational theory of intelligence, besides trying to transform the way we interact with computers, and enlarge the ‘cognitive’ abilities of the computers, thereby opening up many new application areas like Expert Systems, etc. The author has developed an Expert System for the thermal design of wet cooling towers using artificial intelligence as a tool. A cooling tower is a device which is used to cool water by a simultaneous process of heat and mass transfer. Most commonly used type of cooling tower is the one where the temperature of circulating water is reduced by bringing it into direct contact with air. Such towers are called wet cooling towers where the cooling is achieved partly by the evaporation of a fraction of the circulating water and partly by the transfer of sensible heat.